Co-application of a biosolids product and biochar to two coarse-textured pasture soils influenced microbial N cycling genes and potential for N leaching - Shanmugam, Sanjutha; Jenkins, Sasha N.; Mickan, Bede S.; Md Jaafar @ Ahmad Jaafar, Noraini; Mathes, Falko; Solaiman, Zakaria M.; Abbott, Lynette K. (Nature Research, 2021)
Co-application of biochar and biosolids to soil has potential to mitigate N leaching due to physical and chemical properties of biochar. Changes in N cycling pathways in soil induced by co-application of biological amendments could further mitigate N loss, but this is largely unexplored. The aim of this study was to determine whether co-application of a biochar and a modified biosolids product to three pasture soils differing in texture could alter the relative abundance of N cycling genes in soil sown with subterranean clover. The biosolids product contained lime and clay and increased subterranean clover shoot biomass in parallel with increases in soil pH and soil nitrate. Its co-application with biochar similarly increased plant growth and soil pH with a marked reduction in nitrate in two coarse textured soils but not in a clayey soil. While application of the biosolids product altered in silico predicted N cycling functional genes, there was no additional change when applied to soil in combination with biochar. This supports the conclusion that co-application of the biochar and biosolids product used here has potential to mitigate loss of N in coarse textured soils due to N adsoption by the biochar and independently of microbial N pathways.